Survey of Cryptococcal Antigens in Urban Pigeons (Columba livia) in Sao Paulo State, Brazil - Ferreira, Vivian Lindmayer; Raso , Tania de Freitas (International Journal of Poultry Science, 2011)
Cryptococcoses is a zoonosis caused by the saprophyte yeast Cryptococcus neoformans. It has been described in several animals species and frequently it is related with environments where bird’s droppings are accumulated. The aim of the present study was to investigate the presence of antigens of C. neoformans in the blood serum of urban pigeons (Columba livia) in São Paulo and Tatuí cities, Brazil. During a year 240 birds has their serum evaluated, with a latex agglutination test, for the presence of cryptococcal antigens. All the birds showed negative results. Most researches report the identification of C. neoformans in feces present in the environments occupied by pigeons. However, there is little information regarding the investigation of the agent directly on the bird, either by detection of antigen or antibodies. There is no doubt that the fungus remains viable in the dry feces of these birds during years, representing a risk factor for the occurrence of cryptococcoses in susceptible hosts. However, it should be noted that the fungus is often present in the environment due to the presence of substrates favorable to their development. Despite the correlation between the prevalence of C. neoformans in nature and bird excreta, the role of the pigeons themselves in disseminating the fungus still need to be more understood.